Preparation of Gallic Acid-Grafted Chitosan Using Recombinant Bacterial Laccase and Its Application in Chilled Meat Preservation - Zheng, Meixia; Zhang, Chong; Zhou, Ying; Lu, Zhaoxin; Zhao, Haizen; Bie, Xiaomei; Lu, Fengxia (Frontiers in Microbiology, 2018)
To improve the antibacterial and antioxidant properties of chitosan (CS), recombinant bacterial laccase from Bacillus vallismortis fmb-103 (fmb-rL103) was used to catalyze gallic acid (GA) grafting. The structures of grafted chitosans were identified using UV–Vis and FT-IR spectroscopy. After gallic acid grafting, the antibacterial properties of chitosans against Pseudomonas, Acinetobacter, Brochothrix thermosphacta, Escherichia coli, Staphylococcus aureus, Salmonella and listeria monocytogenes were significantly improved. Meanwhile, DPPH free radical scavenging results indicated that the antioxidant properties of the grafted chitosan were also enhanced. The preservative effects of the grafted chitosan on chilled meat were then investigated. For this purpose, the quality indicators of the chilled meat during the storage, including color, total bacterial count, total basic volatile nitrogen (TVB-N) content, thiobarbituric acid reactive substances (TBARS), and pH value were monitored. The results showed that coating with the grafted chitosan retarded the growth of spoilage bacteria, and decreased TVB-N and TBARS values of meat. The shelf life of chilled meat coated by GA-g-CS also extended from xx days to 18 days at 4 °C. These results provided a basis for the future application of the GA-g-CS to chilled meat preservation.